Prospective Association Between Chinese Visceral Adiposity Index and Risk of Stroke Incidence in Middle-aged and Elderly Chinese Population - SHAO Miaomiao; CHEN Zhengzhen (Xiehe Yixue Zazhi)
ObjectiveTo investigate the association between the Chinese visceral adiposity index(CVAI) and the risk of stroke incidence in middle-aged and older adults (≥45 years) using data from the China Health and Retirement Longitudinal Study (CHARLS).MethodsData from the 2015, 2018, and 2020 CHARLS surveys were analyzed, focusing on middle-aged and older adults. The primary outcome was the occurrence of new stroke events (including both hemorrhagic and ischemic strokes) during the follow-up period. Covariates included general demographic characteristics, lifestyle factors, health status, and blood biomarkers. Cox proportional hazards regression models were used to explore the dose-response relationship between CVAI and stroke risk.ResultsA total of 11 432 middle-aged and older adults were included, with a mean age of 60.24±9.56 years. Among them, 6157 (53.86%) were women and 5275(46.14%) were men. Over a median follow-up period of 5 years, 905 individuals(7.92%, 905/11 432) experienced a stroke. After adjusting for demographic and lifestyle covariates, each interquartile range (IQR) increase in CVAI was associated with a 28% higher risk of stroke (HR=1.28, 95% CI: 1.20-1.36). Compared to the first quartile (Q1), the third (Q3: HR=1.60, 95% CI: 1.30-1.97) and fourth quartiles (Q4: HR=2.02, 95% CI: 1.65-2.47) were significantly associated with an increased risk of stroke. Interaction analysis revealed a significant interaction between CVAI and gender (Pfor interaction < 0.001). Restricted cubic spline analysis demonstrated a non-linear relationship between CVAI and stroke risk (Pnonlinear=0.005).ConclusionsHigher CVAI levels are associated with an increased risk of stroke. CVAI serves as an effective biomarker for identifying individuals at high risk of stroke and can inform primary stroke prevention strategies.